Synthetic Biology New Interdisciplinary Science - Nagpal, Madan L.; Boldura, Oana-Maria; Baltă, Cornel; Enany, Shymaa (IntechOpen, 2020)
Synthetic biology gives us a new hope because it combines various disciplines, such as genetics, chemistry, biology, molecular sciences, and other disciplines, and gives rise to a novel interdisciplinary science. We can foresee the creation of the new world of vegetation, animals, and humans with the interdisciplinary system of biological sciences. These articles are contributed by renowned experts in their fields. The field of synthetic biology is growing exponentially and opening up new avenues in multidisciplinary approaches by bringing together theoretical and applied aspects of science.